2020
DOI: 10.3171/2018.8.jns181839
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lipoprotein-associated phospholipase A2 level and its changes in the early stages as predictors of delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVEThe relationship between lipoprotein-associated phospholipase A2 (Lp-PLA2) and various cardiovascular and cerebrovascular diseases is inconsistent. However, the connection between Lp-PLA2 level and delayed cerebral ischemia (DCI) following aneurysmal subarachnoid hemorrhage (aSAH) remains unclear. The objective of this study was to investigate the relationships between the Lp-PLA2 levels in the early stages of aSAH and the occurrence of DCI.METHODSThe authors evaluated 114 patients with aSAH who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Quantifying plasma Lp-PLA 2 is useful for identifying plaque instability, acute coronary syndrome, and other cardiovascular diseases [98,99,100]. Moreover, Lp-PLA 2 is a predictor for incident ischemic stroke severity, early neurological deterioration in patients with acute ischemic stroke, and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage [101,102,103]. However, inhibiting Lp-PLA 2 by darapladib, a synthetic specific small molecular weight inhibitor of platelet-activating factor-acetylhydrolase (PAF-AH), did not yield promising results in clinical trials [104,105].…”
Section: Mechanisms For Increased Circulating Lysophosphatidylcholmentioning
confidence: 99%
“…Quantifying plasma Lp-PLA 2 is useful for identifying plaque instability, acute coronary syndrome, and other cardiovascular diseases [98,99,100]. Moreover, Lp-PLA 2 is a predictor for incident ischemic stroke severity, early neurological deterioration in patients with acute ischemic stroke, and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage [101,102,103]. However, inhibiting Lp-PLA 2 by darapladib, a synthetic specific small molecular weight inhibitor of platelet-activating factor-acetylhydrolase (PAF-AH), did not yield promising results in clinical trials [104,105].…”
Section: Mechanisms For Increased Circulating Lysophosphatidylcholmentioning
confidence: 99%
“…Several studies have mentioned that biochemical indicators could serve as predictive factors of the prognosis in patients with aSAH, such as lipoprotein‐associated phospholipase A2, high‐sensitivity C‐reactive protein 12,13 . However, the change of a single indicator may not provide strong and sufficient clinical evidences for clinicians to diagnose the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have mentioned that biochemical indicators could serve as predictive factors of the prognosis in patients with aSAH, such as lipoprotein-associated phospholipase A2, high-sensitivity C-reactive protein. 12,13 However, the change of a single indicator may not provide strong and sufficient clinical evidences for clinicians to diagnose the diseases. The predictive models are a derivative tool in statistics which are useful to predict the prognostic outcomes on the basis of the pooled evaluations of physical, laboratory, and radiologic examinations.…”
mentioning
confidence: 99%
“…Also, Lp-PLA2 may be a prognostic factor for ischemic stroke severity, as it was observed that patients with high Lp-PLA2 levels had more severe symptoms after stroke and earlier neurological deterioration [129]. Lp-PLA2 in the early stages of aneurysmal subarachnoid hemorrhage might be a new predictive biomarker for the occurrence of delayed cerebral ischemia [130].…”
Section: Lysophosphatidylcholinementioning
confidence: 99%
“…In addition to its diagnostic value in ACS, copeptin proved to be efficient as a prognostic biomarker, being correlated with the 1-year mortality and major complications after an acute coronary event [134]. Studies showed that copeptin levels were correlated with the size of the myocardial infarction and the degree of left ventricular dysfunction and ventricular remodeling [130,135]. Also, in patients with heart failure, copeptin was identified as a valuable prognosis biomarker, being able to predict adverse outcomes and mortality [128,129].…”
Section: Copeptinmentioning
confidence: 99%